Molecular and crystal structure of 2,5-bis[(4-fluorophenyl)iminomethyl]furan - Moira K. Lauer; Gary J. Balaich; Scott T. Iacono; Nathan J. Weeks (Acta Crystallographica Section E: Crystallographic Communications)
The title furan bis(imine) compound, 2,5-bis[(4-fluorophenyl)iminomethyl]furan, C18H12F2N2O, was synthesized by condensation of 2,5-furandicarboxaldehyde with two equivalents of 4-fluoroaniline. The molecular structure consists of a central furan ring symmetrically bound to nearly coplanar iminomethyl groups with N-bonded 4-fluorophenyl rings that are significantly tipped out of the plane of the furan ring. In the crystal structure, the furan ring lies on a twofold rotation axis in space group C2/c with the furan ring and imine groups of adjacent molecules participating in C—H...N interactions to give furan-ring-centered hydrogen-bonded chains extending along [010]. Further cohesion of the crystal structure is achieved by participation of the peripheral 4-fluorophenyl rings in C—H...F hydrogen bonding and edge-to-face C—H...π interactions, resulting in a tri-periodic network. The resulting supramolecular chains formed by C—H...F hydrogen bonding extend in a direction parallel to [101].